Vertebral anomalies in retired rugby players and the impact on bone density calculation of the lumbar spine - Entwistle, I.; Hume, P.; Francis, P.; Hind, K. (Journal of Clinical Densitometry, 2020)
Dual energy X-ray absorptiometry (DXA) lumbar spine bone mineral density (BMD) measurements are subject to artificial elevation in the presence of structural abnormalities that are more common with age and injury, including osteoarthritis, fracture and osteophytes. The aims of this study were to investigate the presence of vertebral abnormalities on DXA scans in retired rugby players and a nonrugby control group, and to explore the effect of vertebral exclusion on the BMD diagnostic outcome. Eigty-seven male retired rugby players and 51 non-rugby controls from the UK Rugby Health Project participated in the study. Lumbar spine, total hip and femoral neck BMD were measured by DXA and scans were analyzed pre and post exclusion of anomalous vertebrae. Data were analyzed by age group to enable application of T-scores (=50 y) and Z-scores (<50 y). From 138 lumbar spine scans, 66 required adjustment. One hundred twenty-two vertebral exclusions were made, and 12 lumbar spine scans (10 in retired rugby athletes) were un-reportable (<2 evaluable vertebrae). Vertebral exclusion significantly lowered lumbar spine BMD across all groups (p<0.01) and lowered the overall lowest T/Z-score. This effect was more pronounced in rugby groups (age <50 y, p < 0.001; age =50 y, p = 0.031) than in the control groups (age <50y, p=0.125; age =50 y, p=0.250). Vertebral abnormalities detected on lumbar spine scans, were highly prevalent and impacted final the T/Z-score in this cohort of retired rugby players. Current guidelines recommend exclusion of abnormalities from lumbar spine scans in adults aged =50 years. Our findings suggest that vertebral exclusions should also be applied to lumbar spine scans performed in those aged <50 years, particularly in former contact sports athletes, given their high risk for vertebral deformity.